2019
DOI: 10.1002/prep.201800357
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Cycling and Ratchet Growth of TATB and PBX 9502

Abstract: The irreversible volume expansion, or ratchet growth, of TATB and PBX 9502 (95 weight% TATB) compactions has been quantified over a wide range of thermal cycles. While the precise TATB texture distributions of these specimen sets are likely different from each other, we believe they are consistent within each set, as the expansion data show reproducibility and consistency. These data provide a baseline characterization of the ratchet growth phenomenon in these materials. The increased expansion that comes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…In Figure 3, the magnitude of change in the CTE values correlates with the high-temper- ature limit (X°C). Elsewhere [2] we have demonstrated that as the upper bound of temperature is increased, the ratchet growth also significantly increases. Figures 3 and 4 distinguish data from ascending temperature ramps (solid symbols) and data from descending ramps (open symbols).…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…In Figure 3, the magnitude of change in the CTE values correlates with the high-temper- ature limit (X°C). Elsewhere [2] we have demonstrated that as the upper bound of temperature is increased, the ratchet growth also significantly increases. Figures 3 and 4 distinguish data from ascending temperature ramps (solid symbols) and data from descending ramps (open symbols).…”
Section: Resultsmentioning
confidence: 80%
“…Some tests were performed with many repeated cycles to the same X(°C) endpoint temperature and other tests were conducted with alternating hot/cold X(°C) endpoint temperatures. Note that the tests listed in Table 1 are a subset of those analyzed earlier [2] for their irreversible thermal expansion, specifically strain values measured at ambient and caused by thermal cycles. Here we analyze the strain evolution during the ascending and descending temperature ramps.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations